Electrochromic polymer film, preparation method, electrochromic device containing electrochromic polymer film and application
Through the in -situ oxidation polymerization method to prepare electricity, the discoloration polymer film is solved, and the existing method requires the problem of conductive base and limited thickness, and achieves the effects of non -conductive base, large -scale production and efficient preparation.
Patent Information
- Application Number
- CN202411969584.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
AI Technical Summary
The existing electrochromic polymer film preparation methods require a conductive substrate, and the film thickness is limited by the substrate conductivity, resulting in high production costs and unsuitable for industrial production.
Adopt the in -situ oxidation polymerization method to reserve the discoloration polymer membrane, which provides a precursor solution that contains the main solvents, auxiliary solvent, oxidant, and phenoto derivative monomer for coating and in situ oxidation polymerization reactions to form electrical discoloration polymerization polymerization aggregation Film.
No conductive base is required to achieve large -scale production and expand the controllable range of thin film thickness, reduce production costs, and the obtained membrane has high reactivity and strong anti -ions, suitable for industrial production.
Smart Images

Figure CN119371697A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochromic materials, and in particular to an electrochromic polymer film, a preparation method, an electrochromic device containing the same, and applications thereof. Background Art
[0002] Electrochromic technology is a technology that allows the reflectivity, transmittance, absorptivity and other optical properties of materials to undergo stable and reversible color changes under the action of an external electric field, thereby achieving active dynamic control of light and solar radiation heat. In appearance, it manifests as a reversible change in color and transparency. At present, the application scenarios of electrochromic technology are concentrated in the fields of automobiles, airplanes, glass curtain walls, mobile phones, such as car rearview mirrors, Boeing 787 aircraft, mobile phone displays, etc.
[0003] The traditional method for synthesizing electrochromic polymer films is electrochemical polymerization, but this method is expensive and not suitable for industrial production. At the same time, this method also requires a conductive substrate, and the film thickness is limited by the conductivity of the substrate. Summary of the invention
[0004] In view of the above problems existing in the prior art, the first aspect of the present application provides a method for preparing an electrochromic polymer film, the preparation method comprising: providing a precursor solution, wherein the precursor solution comprises a main solvent, a secondary solvent, an oxidant and a thiophene derivative monomer, the main solvent and the secondary solvent are different, and the secondary solvent can form a complex with at least part of the metal ions in the oxidant; applying the precursor solution to the surface of a substrate, causing the thiophene derivative monomer to undergo an in-situ oxidative polymerization reaction to form an electrochromic polymer film, wherein the thiophene derivative monomer comprises one or more of the following organic substances: .
[0005] The second aspect of the present application also provides an electrochromic polymer film, the electrochromic polymer film comprising an organic substance represented by the following structural formula: , n is 1 to 5, and / or is prepared by the preparation method provided in the present application.
[0006] The third aspect of the present application also provides an electrochromic device, including an electrochromic layer, the electrochromic layer comprising the electrochromic polymer film provided in the present application; optionally, the transmittance of the electrochromic device in the wavelength range of 590nm to 630nm changes by no less than 25%, and the transmittance in the wavelength range of 390nm to 450nm changes by no less than 10%; optionally, the transmittance of the electrochromic device in the wavelength range of 540nm to 560nm changes by no less than 20%, and the transmittance in the wavelength range of 660nm to 740nm changes by no less than 30%; preferably, the electrochromic device includes a membrane switch, electronic paper, an electronic price tag, an electrochromic display, a smart window or a vehicle-mounted head-up display.
[0007] The fourth aspect of the present application also provides an application of the above electrochromic polymer film in the field of electrochromism.
[0008] Beneficial effects: The method for preparing the electrochromic polymer film provided in the present application has the following advantages: (1) Traditional methods mostly use electropolymerization to prepare electrochromic polymer films, so the substrate needs to be conductive. This application uses in-situ oxidative polymerization, so there is no need for a conductive substrate, which can achieve large-scale production. At the same time, this method is compatible with industrial coating technologies (such as blade coating, slit coating and roll-to-roll processing), making it more controllable, scalable and efficient.
[0009] (2) The controllable range of film thickness is wider.
[0010] Since electrochromic polymer films are generally not conductive, conventional electropolymerization methods will turn the film into an insulator after it reaches a certain thickness, making it impossible to deposit and thicken it further. However, the preparation method used in this application uses direct coating with a coating liquid, so there is no such limitation. This allows the thickness of the obtained polymer film to be more controllable.
[0011] (3) The polymer film obtained by the above preparation method is also doped with highly reactive and strong counterions, such as perchlorate (ClO4 - ions). When preparing electrochromic devices, there is no need to use electrolytes containing lithium salts, etc., which can reduce costs and avoid the use of explosive chemicals.
[0012] (4) Lower cost and more compatible with existing industrial equipment If the traditional electropolymerization method is used to prepare industrial-scale production, it is necessary to purchase a huge electrolytic cell filled with organic solvents and prepare electrochromic polymer films one by one through a method similar to electroplating, which is costly and energy-intensive (so no company currently uses this method to mass-produce organic electrochromic polymer films on the market). This method can directly use the current industrial-grade printing and coating equipment to produce electrochromic polymer films, reducing the cost of production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The chemical formation mechanism of the polythiophene electrochromic polymer film in the preparation method of the electrochromic polymer film provided by the present application is shown.
[0014] Figure 2 Figure 1 is a morphological feature diagram of an electrochromic polymer film, wherein A shows the morphological features of an electrochromic polymer film made using a secondary solvent in Example 1 of the present application, and the substrate size is 400 mm 2 glass, B shows the morphological characteristics of the electrochromic polymer film made without using a secondary solvent in Example 1, and the substrate size is 400 mm 2 of glass.
[0015] Figure 3 The morphology of the film prepared by the method in Example 1-1 of the present application is shown under an atomic force microscope.
[0016] Figure 4 The UV-visible-near infrared transmittance of the electrochromic polymer film prepared in Example 5-1 of the present application is shown.
[0017] Figure 5 The UV-visible-near infrared transmittance of the electrochromic polymer film prepared in Example 5-2 of the present application is shown.
[0018] Figure 6 A schematic diagram of the structure of a typical electrochromic device provided in this application.
[0019] Figure 7 The UV-visible-near infrared transmittance of the electrochromic device prepared in Example 6-1 of the present application is shown.
[0020] Figure 8 The UV-visible-near infrared transmittance of the electrochromic device prepared in Example 6-2 of the present application is shown.
[0021] Fig. 9 A comparison diagram of the electrochromic device after laser etching and patterning in Example 6-1 of the present application after applying a forward voltage and a reverse voltage is shown, wherein A represents the application of a forward voltage and B represents the application of a reverse voltage.
[0022] Fig.10 A comparison diagram of the electrochromic device after laser etching and patterning in Example 6-2 of the present application after applying a forward voltage and a reverse voltage is shown, wherein A represents the application of a forward voltage and B represents the application of a reverse voltage. DETAILED DESCRIPTION
[0023] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0024] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0025] In view of the technical problems existing in the prior art, the first aspect of the present application provides a method for preparing an electrochromic polymer film, the preparation method comprising: providing a precursor solution, wherein the precursor solution comprises a main solvent, a secondary solvent, an oxidant and a thiophene derivative monomer, wherein the secondary solvent can form a complex with at least part of the metal ions in the oxidant; applying the precursor solution to the surface of a substrate, causing the thiophene derivative monomer to undergo an in-situ oxidative polymerization reaction to form an electrochromic polymer film, wherein the thiophene derivative monomer comprises one or more of the following organic substances: .
[0026] The chemical formation mechanism of polythiophene electrochromic polymer films is shown in Figure 1 . Thiophene derivative monomers
[0027] Since the above preparation process is an in-situ oxidative polymerization process, the entire reaction is carried out in a solution environment. In order to improve the reaction degree of the in-situ oxidative polymerization reaction, the thiophene derivative monomer needs to have good solubility in the solvent. Compared with thiophene derivative monomers of other structures, the preparation method of the thiophene derivative monomer shown in the above structural formula is simple, and the electrochromic film obtained after polymerization has relatively excellent electrochromic properties. In some embodiments of the present application, the thiophene derivative monomer includes but is not limited to at least one of 5,5'-(2,5-difluoro-1,4-phenylene)bis(2,3-dihydro-[3,4-b]thiophene-1,4-dioxane), 2,2'-(2,5-difluoro-1,4-phenylene)dithiophene and 3,6-bis(2,3-dihydro-[3,4-b]thiophene-1,4-dioxane-5-yl)-9-methyl-9H-carbazole. Compared with other thiophene derivative monomers, the electrochromic polymer films prepared from the above-mentioned thiophene derivative monomers have higher contrast before and after color change, wider operating voltage window, shorter response time, better stability and service life.
[0028] In some embodiments of the present application, the weight percentage of the thiophene derivative monomer in the precursor solution is 0.01-5 wt%. Optionally, the weight percentage of the thiophene derivative monomer in the precursor solution is 0.01 wt%, 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, or a range formed by any two of the above values. Preferably, the weight percentage of the thiophene derivative monomer in the precursor solution is 0.2-0.8 wt%. Main solvent
[0029] The main solvent is used to dissolve the thiophene derivative monomer, and it is necessary to select a solvent type with a high solubility for such non-polar, low-solubility organic matter. In some embodiments of the present application, the main solvent includes at least one of chloroform, chlorobenzene, toluene, xylene, acetonitrile and dimethyl sulfoxide. Compared with other solvents, the above-mentioned solvents have a better solubility for the thiophene derivative monomer, which is beneficial to improve the yield and thickness of the electrochromic polymer film finally obtained. In one embodiment, the main solvent includes dimethyl sulfoxide (DMSO), which is beneficial to improve the compactness of the electrochromic polymer film.
[0030] In some embodiments of the present application, in the precursor solution, the weight percentage of the main solvent is 50-90 wt %, for example, the weight percentage of the main solvent is 50 wt %, 55 wt %, 60 wt %, 65 wt %, 70 wt %, 75 wt %, 80 wt %, 85 wt %, 90 wt %, or a range formed by any of the above values. Oxidants
[0031] The oxidant is used to participate in the in-situ oxidative polymerization reaction. In some embodiments of the present application, the oxidant includes at least one of Fe(ClO4)3, Fe(OTf)3 and Fe(OTs)3, and preferably the oxidant includes Fe(ClO4)3. Secondary solvent
[0032] In the oxidative polymerization reaction in the presence of Fe (III), the oxidant has a very strong reactivity in polar solvents, resulting in a short service life of the precursor solution and uneven film formation during in-situ oxidative polymerization. In order to solve this problem, the applicant introduced a secondary solvent during the preparation of the electrochromic polymer film.
[0033] The main function of the secondary solvent is to react with at least some of the metal ions (such as Fe 3+ ) to form an unstable complex to slow down the oxidative polymerization reaction rate and obtain a higher uniformity of the film, so cyclic amides and other solvents containing amide groups or P=O double bonds are preferred. In some embodiments of the present application, the secondary solvent includes at least one of cyclic amides, chain amides, cyclic ureas, and chain alkyl ureas, preferably at least one of the compounds of formula (A), formula (B), formula (C), formula (D), formula (E), and formula (F). .
[0034] In formula (A), n is an integer from 1 to 8, and R is independently selected from C1-C8 alkyl, preferably C 1- C6 alkyl, further preferably methyl, ethyl, propyl, butyl, pentyl or hexyl; In formula (B), n is an integer from 0 to 8, and R is independently selected from C1-C8 alkyl, preferably C1-C6 alkyl, and further preferably methyl, ethyl, propyl, butyl, pentyl or hexyl; In formula (C), R is independently selected from C1-C8 alkyl, preferably C1-C6 alkyl, and more preferably methyl, ethyl, propyl, butyl, pentyl or hexyl; In formula (D), R is independently selected from C1-C8 alkyl, preferably C1-C6 alkyl, and further preferably methyl, ethyl, propyl, butyl, pentyl or hexyl; In formula (E), R is independently selected from C1-C8 alkyl, preferably C1-C6 alkyl, and more preferably methyl, ethyl, propyl, butyl, pentyl or hexyl; In formula (F), R is independently selected from C1-C8 alkyl, preferably C1-C6 alkyl, and more preferably methyl, ethyl, propyl, butyl, pentyl or hexyl.
[0035] In some embodiments of the present application, the weight percentage of the secondary solvent in the precursor solution does not exceed 50wt%, preferably 5-50wt%, such as 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, or any range formed by the above values; more preferably 5-15wt%.
[0036] By adjusting the type and amount of the auxiliary solvent, the rate of the polymerization reaction can be controlled, making the electrochromic polymer film dense and uniform. In addition, these auxiliary solvents can adjust the viscosity of the precursor solution and form electrochromic polymer films of different thicknesses (such as 20-1500 nm) and different visible light transmittances. Control experiments have shown that the use of a method without auxiliary solvents will result in too fast a reaction rate, causing the polymer to agglomerate and shrink on the substrate, resulting in a film with a rough surface and even large holes ( Figure 2 ). Other components
[0037] In some embodiments of the present application, the precursor solution also includes a polyethylene glycol copolymer. Adding a polyethylene glycol copolymer to the above-mentioned precursor solution can adjust its viscosity, thereby affecting the thickness and visible light transmittance of the electrochromic polymer film finally obtained. In some embodiments, the polyethylene glycol copolymer includes a triblock copolymer of polyethylene glycol-polypropylene glycol-polyethylene glycol, and further preferably, the mass average molecular weight of the triblock copolymer of polyethylene glycol-polypropylene glycol-polyethylene glycol is 2900-14600. The mass average molecular weight includes but is not limited to the above range, and limiting it to the above range can adjust the thickness and visible light transmittance of the electrochromic polymer film in a larger range, thereby increasing its market share. In order to make the electrochromic polymer film have a more suitable thickness, a suitable degree of polymerization, and facilitate the subsequent film cleaning step, preferably, the mass average molecular weight of the triblock copolymer of polyethylene glycol-polypropylene glycol-polyethylene glycol is 2900-8400.
[0038] In some embodiments of the present application, in the precursor solution, the weight percentage of the polyethylene glycol copolymer is 2-6 wt %, for example, the weight percentage of the polyethylene glycol copolymer is 2 wt %, 2.5 wt %, 3 wt %, 3.5 wt %, 4 wt %, 4.5 wt %, 5 wt %, 5.5 wt %, 6 wt %, or any range formed by the above values.
[0039] In some embodiments of the present application, the precursor solution further comprises an auxiliary agent, preferably a leveling agent. The addition of the leveling agent is beneficial to improving the fluidity and surface appearance of the precursor solution coating process, so as to enhance the formation of a flat, smooth, and defect-free surface of the coating during the drying or curing process, thereby improving the performance of the electrochromic polymer film finally obtained.
[0040] In some embodiments of the present application, after coating the precursor solution on the substrate surface, the method for preparing the electrochromic polymer film further includes: post-treating the precursor solution on the substrate surface, wherein the post-treatment step includes at least one of washing and drying.
[0041] In some embodiments, the reaction temperature of the in-situ oxidative polymerization reaction is 50 to 180°C. The reaction temperature of the in-situ oxidative polymerization reaction includes but is not limited to the above range, and limiting it within the above range is conducive to improving the reaction sufficiency of the in-situ oxidative polymerization reaction, thereby increasing the difference in the visible light color change rate before and after the color change. For example, the reaction temperature of the in-situ oxidative polymerization reaction is 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, or the range formed by any of the above values, preferably 80 to 180°C.
[0042] The time of the polymerization reaction is adjusted according to the degree of the polymerization reaction. Preferably, the time of the polymerization reaction includes but is not limited to 0.1 to 20 minutes. For example, the time of the polymerization reaction is 0.1 min, 0.5 min, 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min, 9.5 min, 10 min, 10.5 min, 11 min, 11.5 min, 12 min, 12.5 min, 13 min, 13.5 min, 14 min, 14.5 min, 15 min, 15.5 min, 16 min, 16.5 min, 17 min, 17.5 min, 18 min, 18.5 min, 19 min, 19.5 min, 20 min, or the range formed by any of the above values. Substrate
[0043] Since the in-situ oxidative polymerization process is not an electropolymerization process, the substrate does not need to be conductive. Therefore, in the above preparation method, the substrate can be a conductive or non-conductive substrate. In one embodiment, glass, ITO glass, or PET is used as the substrate. Coating process
[0044] The method of coating the precursor solution on the surface of the substrate may be a commonly used method in the art, such as spin coating, dip coating, slot die coating or inkjet printing.
[0045] Unwanted components can be removed through the washing process. In some embodiments of the present application, the product after the polymerization reaction is immersed in a solvent bath, and the unreacted oxidant, inert copolymer and side solvent components are washed with ethanol / methanol solvent; the washed film is then dried (preferably at 50°C to 80°C) to obtain a uniform electrochromic polymer film.
[0046] The second aspect of the present application also provides an electrochromic polymer film, the electrochromic polymer film comprising an organic substance represented by the following structural formula: , Wherein n is 1 to 5, and / or the electrochromic polymer film is prepared by the preparation method provided in the present application. Optionally, the degree of polymerization n is 1, 2, 3, 4, 5 or any range formed by the above values.
[0047] In some embodiments of the present application, the thickness of the electrochromic polymer film ranges from 10nm to 500μm, and / or the operating voltage of the electrochromic polymer film is -1.5V to 1.5V, and / or the maximum electrochromic contrast wavelength ranges of the electrochromic polymer film before and after color change are 580nm to 620nm, 695nm to 735nm and 405nm to 445nm, respectively, and the thickness is 10nm to 500μm. In some preferred embodiments, the maximum electrochromic contrast wavelength ranges of the electrochromic polymer film before and after color change are 600nm, 716nm, 423nm, respectively, and the thickness is 10nm to 500μm.
[0048] The third aspect of the present application also provides an electrochromic device, including an electrochromic layer, wherein the electrochromic layer comprises the electrochromic polymer film provided in the present application. Preferably, the electrochromic device includes a membrane switch, electronic paper, an electronic price tag, an electrochromic display, a smart window or a vehicle head-up display.
[0049] In some embodiments of the present application, the color change range of the above-mentioned electrochromic device is 6-1 (L=70, a=-4, b=15 to L=-49, a=-5, b=-24) and 6-2 (L=34, a=34, b=-17 to L=44, a=-11, b=-24) using the International Commission on Illumination (CIE) Lab color coordinate system.
[0050] The fourth aspect of the present application also provides an application of the above electrochromic polymer film in the field of electrochromism.
[0051] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0052] The equipment used in the embodiments and comparative examples and the parameter calculation method are as follows: Equipment and methods: Coating: Prepared in a clean room using a coating machine. The average transmittance of the glass in the visible light range is 90%.
[0053] UV-Vis-NIR spectroscopy: Shimadzu UV-Vis spectrophotometer UV-2600 was used for detection with a direct detector without an integrating sphere and a slit width of 5 nm.
[0054] Thickness: Use a KLA Alpha-Step D-600 stylus profilometer to test, scrape three times, then take the average to account for thickness and calculate the average deviation.
[0055] Visible light transmittance: tested using a TH-100 haze meter.
[0056] The names and structures of representative secondary solvents used in the present invention are shown in Table 1.
[0057] The names and structures of representative thiophene derivative monomers used in the present invention are shown in Table 2.
[0058] .
[0059] .
[0060] [Example 1] Example 1-1 The one-step process for preparing conductive polymer film is as follows: The main solvent chloroform and the secondary solvent CLM were mixed in proportion to form a solvent system. PEG-PPG-PEG (Mw: 8400) and the solid oxidant Fe(ClO4)3 were added to the above solvent system and mixed thoroughly to form solution A. In solution A, the content of chloroform was 87 wt%, the content of CLM was 2 wt%, the content of PEG-PPG-PEG was 8 wt%, and the content of the solid oxidant Fe(ClO4)3 was 3 wt%. Next, 10 mg of Cz-EDOT was added to 1.5 mL of solution A to form solution B. Solution B was heated at 400 mm for 5 min. 2 The film was spin-coated on glass and annealed at 120°C for 5 min. After that, it was washed in an ethanol bath at room temperature for 10 min (three times). It was then dried at 60°C for 30 min to obtain an electrochromic polymer film. Its properties are shown in Table 3. The electrochromic process from color 1 (color when forward voltage is applied) to color 2 (color when reverse voltage is applied) takes 10 -5 The film was treated with 10 mol / L hydrazine / ethanol solution to simulate the process. -5 mol / L hydrazine / ethanol solution was added dropwise to the electrochromic polymer film in the color 2 (color when the reverse voltage was applied) state until it was completely covered, and then the excess hydrazine / ethanol solution was evenly removed by spin coating. The obtained sample was heated to 60°C and dried for 5 minutes to convert the electrochromic polymer film to color 1 (color when the forward voltage was applied).
[0061] In Examples 1-2 to 1-8, we conducted experiments under the same experimental conditions as in Example 1-1 but with different secondary solvents (see Table 3).
[0062] .
[0063] In this application, “visible light transmittance of colors 1 and 2” refers to the average transmittance in the visible light range (390-780 nm).
[0064] Table 3 summarizes the average visible light transmittance of the film before and after the color change and the transmittance at the maximum color change wavelength (600 nm) at a specific film thickness. It can be seen from the table that the introduction of the auxiliary solvents shown in Table 1 can effectively control the reaction rate of the in-situ oxidative polymerization, thereby improving the uniformity of the film. By adjusting the type of auxiliary solvent, the rate of the in-situ oxidative polymerization reaction can be controlled, so that films with different thicknesses and different transmittance characteristics can be prepared within the same reaction time.
[0065] Figure 2 Shown is a substrate size of 400 mm 2 Film morphology. The figure shows that the film prepared in pure chloroform without the addition of co-solvent (B) shows crystal formation of the oxidant and a non-uniform film morphology. However, after adding the co-solvents shown in Table 1, the film became uniform and highly ordered (A). Here, the co-solvent adjusts the appropriate viscosity, polarity, and solubility to form a better film through electrostatic interactions with the oxidant and PEG-PPG-PEG polymer. In this system, the PEG-PPG-PEG polymer guides the polymer chain growth in a systematic order used in gas phase polymerization techniques. Figure 3 The morphology of the film obtained by the method in Example 1-1 under an atomic force microscope is shown. The roughness of the film is only 2.38 nm, and the surface is very smooth and uniform.
[0066] [Example 2] Example 2-1 The main solvent chloroform and the secondary solvent CLM were mixed in proportion to form a solvent system. PEG-PPG-PEG (Mw: 2900) and the solid oxidant Fe(ClO4)3 were added to the above solvent system and mixed thoroughly to form solution A. In solution A, the content of chloroform was 87 wt%, the content of CLM was 2 wt%, the content of PEG-PPG-PEG was 8 wt%, and the content of the solid oxidant Fe(ClO4)3 was 3 wt%. Next, 10 mg of Cz-EDOT was added to 1.5 mL of solution A to form solution B. Solution B was heated at 400 mm for 5 min. 2 The film was spin-coated on glass and annealed at 120°C for 5 min. After that, it was washed in an ethanol (or acetonitrile) bath at room temperature for 10 min (three times). It was then dried at 60°C for 30 min to obtain an electrochromic polymer film. Its properties are shown in Table 4. The electrochromic process from color 1 (color when forward voltage is applied) to color 2 (color when reverse voltage is applied) takes 10 -5 The film was treated with 1 mol / L hydrazine / ethanol solution for simulation.
[0067] In Examples 2-2 to 2-5, we performed experiments under the same experimental conditions as in Example 2-1 by replacing PEG-PPG-PEG with different molecular weights (see Table 4).
[0068] .
[0069] Table 4 shows the properties of the films obtained using PEG-PPG-PEG with different molecular weights. As can be seen from Table 4, as the molecular weight of PEG-PPG-PEG increases, the viscosity of solution B gradually increases, so that the thickness of the final electrochromic polymer film gradually increases. It is particularly noted that since PEG-PPG-PEG with Mw = 14600 is insoluble in ethanol, acetonitrile is required for washing.
[0070] [Example 3] Example 3-1
[0071] The main solvent chloroform and the secondary solvent CLM were mixed in proportion to form a solvent system. PEG-PPG-PEG (Mw: 8400) and the solid oxidant Fe(ClO4)3 were added to the above solvent system and mixed thoroughly to form solution A. In solution A, the content of chloroform was 87 wt%, the content of CLM was 2 wt%, the content of PEG-PPG-PEG was 8 wt%, and the content of the solid oxidant Fe(ClO4)3 was 3 wt%. Next, 10 mg of Cz-EDOT was added to 1.5 mL of solution A to form solution B. Solution B was heated at 400 mm for 5 min. 2 The film was spin-coated on glass and then heated at 60 ℃ annealing for 5 min. Afterwards, it was washed in an ethanol bath at room temperature for 10 min (three times). It was then dried at 60 ℃ for 30 min to obtain an electrochromic polymer film, and its properties are shown in Table 5. The electrochromic process from color 1 (color when forward voltage is applied) to color 2 (color when reverse voltage is applied) was 10 -5 The film was treated with 1 mol / L hydrazine / ethanol solution for simulation.
[0072] In Examples 3-2 to 3-6, we performed annealing treatment at 80-180°C under the same solution formulation as in Example 3-1 (see Table 5).
[0073] .
[0074] Table 5 shows the effect of annealing temperature on the properties of electrochromic polymer film. As can be seen from Table 5, the effect of annealing temperature on film thickness is small. When the annealing temperature is low (60°C), the transmittance of the electrochromic polymer film before and after color change is higher than that at other temperatures, and the difference in transmittance before and after color change becomes smaller. This is because the polymerization reaction is not sufficient at a lower temperature, resulting in a decrease in film thickness and a small polymer molecular weight.
[0075] [Example 4] Example 4-1
[0076] The main solvent chloroform and the secondary solvent CLM were mixed in proportion to form a solvent system. PEG-PPG-PEG (Mw: 8400) and the solid oxidant Fe(ClO4)3 were added to the above solvent system and mixed thoroughly to form solution A. In solution A, the content of chloroform was 87 wt%, the content of CLM was 2 wt%, the content of PEG-PPG-PEG was 8 wt%, and the content of the solid oxidant Fe(ClO4)3 was 3 wt%. Next, 10 mg of Cz-EDOT was added to 1.5 mL of solution A to form solution B. Solution B was heated at 400 mm for 5 min. 2 The film was spin-coated on glass and annealed at 120°C for 5 min. After that, it was washed in an ethanol bath at room temperature for 10 min (three times). It was then dried at 60°C for 30 min to obtain an electrochromic polymer film. Its properties are shown in Table 6. The electrochromic process from color 1 (color when forward voltage is applied) to color 2 (color when reverse voltage is applied) takes 10 -5 The film was treated with 1 mol / L hydrazine / ethanol solution for simulation.
[0077] In Examples 4-2 to 4-4, we carried out experiments by replacing different main solvents under the same experimental conditions as in Example 4-1 (see Table 6).
[0078] .
[0079] Table 6 shows the effect of changing the main solvent on the properties of the electrochromic polymer film. As can be seen from Table 6, this in-situ polymerization method is adaptable to a variety of solvents. The film properties obtained from chloroform and chlorobenzene are very similar. DMSO has a higher boiling point and can also reduce the rate of oxidative polymerization reaction, making the resulting film denser and thinner. Acetonitrile has poor solubility in Cz-EDOT, so a thinner electrochromic polymer film is also obtained.
[0080] [Example 5] Example 5-1
[0081] The main solvent chloroform and the secondary solvent CLM were mixed in proportion to form a solvent system. PEG-PPG-PEG (Mw: 8400) and the solid oxidant Fe(ClO4)3 were added to the above solvent system and mixed thoroughly to form solution A. In solution A, the content of chloroform was 87 wt%, the content of CLM was 2 wt%, the content of PEG-PPG-PEG was 8 wt%, and the content of the solid oxidant Fe(ClO4)3 was 3 wt%. Next, 10 mg of Cz-EDOT was added to 1.5 mL of solution A to form solution B. Solution B was heated at 400 mm for 5 min. 2 The film was spin-coated on glass and annealed at 120°C for 5 min. After that, it was washed in an ethanol bath at room temperature for 10 min (three times). It was then dried at 60°C for 30 min to obtain an electrochromic polymer film. Its properties are shown in Table 6. The electrochromic process from color 1 (color when forward voltage is applied) to color 2 (color when reverse voltage is applied) takes 10 -5 The film was treated with 1 mol / L hydrazine / ethanol solution for simulation.
[0082] In Examples 5-2 and 5-3, we conducted experiments using F-EDOT and F-thiophene as monomers under the same experimental conditions as in Example 5-1 (see Table 7).
[0083] .
[0084] Table 7 shows the properties of electrochromic polymer films made using three different thiophene derivative monomers, and the degree of polymerization n of the electrochromic polymer films is 1 to 3. As can be seen from Table 7, this solution system and preparation process can be used for one-step polymerization-coating of thiophene derivative electrochromic polymer films, and has excellent substrate tolerance and universality. Figure 4 and Figure 5 UV-visible-near-infrared absorption spectra of the electrochromic polymer films prepared in Examples 5-1 and 5-2 in color 1 (color when a forward voltage is applied) and color 2 (color when a reverse voltage is applied), respectively.
[0085] [Example 6] Example 6-1
[0086] The solution in Example 5-1 was spread on a 1600 mm 2 After forming the film on the ITO glass, it was annealed at 120℃ for 5min. After that, it was washed in an ethanol bath at room temperature for 10min (three times). Then it was dried at 60℃ for 30min to obtain an electrochromic polymer film uniformly attached to the transparent electrode.
[0087] The ion storage layer (neutral PEDOT) attached to the transparent electrode was made using a slightly modified method previously reported in the literature ( DOI: 10.1021 / acs. chemmater .6b01035 ).
[0088] The UV-curable electrolyte was scraped onto the electrochromic polymer film, and then the ion storage layer was covered on top and the bubbles were discharged. The electrolyte was cured by UV irradiation for 3 minutes to obtain an electrochromic device with the structure of glass / ITO electrode / electrochromic polymer film / electrolyte / ion storage layer / ITO electrode / glass. The performance parameters of the electrochromic device are shown in Table 7.
[0089] Example 6-2, we conducted experiments using the solution in Example 5-2 under the same experimental conditions as Example 6-1 (see Table 8).
[0090] Figure 6 Schematic diagram of the structure of the electrochromic device. Figure 7 and Figure 8 UV-visible-near-infrared absorption spectra of the electrochromic polymer films prepared in Examples 6-1 and 6-2 in color 1 (color when a forward voltage is applied) and color 2 (color when a reverse voltage is applied), respectively. Fig. 9 and Fig.10 This is an example of an electrochromic device after laser etching. The color change range of the electrochromic device is 6-1 (L=70, a=-4, b=15 to L=-49, a=-5, b=-24) and 6-2 (L=34, a=34, b=-17 to L=44, a=-11, b=-24) using the International Commission on Illumination (CIE) Lab color coordinate system.
[0091] .
[0092] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A method for preparing an electrochromic polymer film, characterized in that: The preparation method of the electrochromic polymer film comprises: Providing a precursor solution, wherein the precursor solution comprises a main solvent, a secondary solvent, an oxidant and a thiophene derivative monomer, the main solvent and the secondary solvent are different, and the secondary solvent can form a complex with at least part of the metal ions in the oxidant; The precursor solution is applied to the surface of the substrate to cause the thiophene derivative monomer to undergo an in-situ oxidative polymerization reaction to form an electrochromic polymer film, wherein the thiophene derivative monomer includes one or more of the following organic substances: 。 2. The method for preparing an electrochromic polymer film according to claim 1, characterized in that: The thiophene derivative monomer includes at least one of 5,5'-(2,5-difluoro-1,4-phenylene)bis(2,3-dihydro[3,4-b]thiophene-1,4-dioxane), 2,2'-(2,5-difluoro-1,4-phenylene)dithiophene and 3,6-bis(2,3-dihydro[3,4-b]thiophene-1,4-dioxane-5-yl)-9-methyl-9H-carbazole.
3. The method for preparing an electrochromic polymer film according to claim 1, characterized in that: The method for preparing the electrochromic polymer film comprises any one of the following conditions: (1) The reaction temperature of the in-situ oxidative polymerization reaction is 50 to 180°C; (2) The reaction time of the in-situ oxidative polymerization reaction is 0.1 to 20 minutes; (3) The main solvent includes at least one of chloroform, chlorobenzene, toluene, xylene, acetonitrile and dimethyl sulfoxide; (4) The secondary solvent includes at least one of cyclic amide, chain amide, cyclic urea, and chain alkyl urea; (5) The oxidant includes at least one of Fe(ClO4)3, Fe(OTf)3 and Fe(OTs)3.
4. The method for preparing an electrochromic polymer film according to claim 3, characterized in that: When the method for preparing the electrochromic polymer film includes condition (4), the secondary solvent includes at least one of the compound of formula (A), the compound of formula (B), the compound of formula (C), the compound of formula (D), the compound of formula (E) and the compound of formula (F), , In formula (A), n is an integer from 1 to 8, and R is independently selected from C1-C8 alkyl; In formula (B), n is an integer from 0 to 8, and R is independently selected from C1-C8 alkyl; In formula (C), R is independently selected from C1-C8 alkyl; In formula (D), R is independently selected from C1-C8 alkyl; In formula (E), R is independently selected from C1-C8 alkyl; In formula (F), R is independently selected from C1-C8 alkyl.
5. The method for preparing an electrochromic polymer film according to any one of claims 1 to 4, characterized in that: The precursor solution also includes a polyethylene glycol copolymer, and the polyethylene glycol copolymer includes a triblock copolymer of polyethylene glycol-polypropylene glycol-polyethylene glycol with a mass average molecular weight of 2900-14600.
6. The method for preparing an electrochromic polymer film according to claim 5, characterized in that: The polyethylene glycol copolymer includes a triblock copolymer of polyethylene glycol-polypropylene glycol-polyethylene glycol with a mass average molecular weight of 2900-8400.
7. The method for preparing an electrochromic polymer film according to claim 5, characterized in that: The precursor solution satisfies any one of the following conditions: (1) In the precursor solution, the weight percentage of the thiophene derivative monomer is 0.01 to 5 wt %; (2) In the precursor solution, the weight percentage of the main solvent is 50 to 90 wt %; (3) In the precursor solution, the weight percentage of the secondary solvent does not exceed 50wt%; (4) In the precursor solution, the weight percentage of the polyethylene glycol copolymer is 2 to 6 wt %; (5) The precursor solution also includes an auxiliary agent.
8. The method for preparing an electrochromic polymer film according to claim 7, wherein when the precursor solution satisfies condition (1), the weight percentage of the thiophene derivative monomer in the precursor solution is 0.2-0.8 wt %; When the precursor solution satisfies condition (3), the weight percentage of the secondary solvent in the precursor solution is 5-50wt%; When the precursor solution satisfies condition (5), the auxiliary agent includes a leveling agent.
9. The method for preparing an electrochromic polymer film according to any one of claims 1 to 4, characterized in that: After the precursor solution is coated on the substrate surface, the method for preparing the electrochromic polymer film further comprises: post-treating the precursor solution on the substrate surface, wherein the post-treating step comprises at least one of washing and drying.
10. An electrochromic polymer film, characterized in that: The electrochromic polymer film includes an organic substance represented by the following structural formula: , Wherein n is 1-5, and / or the electrochromic polymer film is prepared by the preparation method according to any one of claims 1 to 9.
11. The electrochromic polymer film according to claim 10, characterized in that The thickness of the electrochromic polymer film is in the range of 10 nm to 500 μm, and / or the working voltage of the electrochromic polymer film is in the range of -1.5 V to 1.5 V, and / or the maximum electrochromic contrast wavelength ranges of the electrochromic polymer film before and after color change are 580 nm to 620 nm, 695 nm to 735 nm, and 405 nm to 445 nm, respectively.
12. An electrochromic device, comprising an electrochromic layer, characterized in that: The electrochromic layer comprises the electrochromic polymer film according to claim 10 or 11.
13. The electrochromic device according to claim 12, characterized in that: The transmittance of the electrochromic device changes by no less than 25% in the wavelength range of 590nm to 630nm, and by no less than 10% in the wavelength range of 390nm to 450nm; or the transmittance of the electrochromic device changes by no less than 20% in the wavelength range of 540nm to 560nm, and by no less than 30% in the wavelength range of 660nm to 740nm.
14. The electrochromic device according to claim 12, characterized in that: The electrochromic device includes a membrane switch, electronic paper, an electronic price tag, an electrochromic display, a smart window or a vehicle head-up display.
15. Use of the electrochromic polymer film according to claim 10 or 11 in the field of electrochromism.
Citation Information
Patent Citations
Electrochromic polymer employing dibenzothiophene or dibenzofuran as a center structure
CN104479113A
Electrochromic polymer containing carbazole structure, preparation method, polymer film and application
CN112430312A
Electrochromic polymer, electrochromic device and preparation method thereof
CN115160544A
High transparency electrochromic polymers
CN117784488A
Conductive polymer precursor solution, conductive polymer film, preparation method and application
CN119119426A
Cited By
Electrochromic polymer film, preparation method, electrochromic device comprising electrochromic polymer film, and application
WO2026145388A1